Pengaruh Perbedaan Jenis Bahan terhadap Hasil Teknik Origami Spiral pada Lengan Balero - Kamila, Aisyah Kurnia; Puspaneli, Puspaneli; Ernawati, Ernawati; Hadiastuti, Hadiastuti (Jurnal Ragam Pengabdian, 2026)
This research was motivated by the need for knowledge about the effect of different textile materials on the finished results of the spiral pleated origami technique on balero sleeves, since fabric characteristics such as thickness, stiffness, and drape are presumed to affect fold stability, volume, and aesthetic value. This study describes the finished balero sleeves made with the spiral pleated origami technique using bridal satin, mikado silk, and shantung satin, viewed from fold stability, volume, and aesthetics, and determines whether differences in material type produce different results. This is an experimental study with a quantitative approach. Data were collected using a questionnaire assessed by 18 panelists (3 experts and 15 trained panelists from the Fashion Design Study Program, IKK FPP UNP), then analyzed descriptively and inferentially through normality, homogeneity, one-way ANOVA, and Post Hoc Bonferroni tests using SPSS version 26. Results show the mikado silk balero obtained the highest percentage at 83.70% (very suitable), followed by bridal satin at 75.54% (suitable) and shantung satin at 62.88% (fairly suitable). The one-way ANOVA test showed a significance value of 0.000, below 0.05, meaning Ha is accepted and Ho rejected. It can be concluded that material type significantly affects the stability, volume, and aesthetics of balero sleeves, with mikado silk as the most optimal material for this technique.